The visceral and liver fat are significantly associated with the prevalence of hyperuricemia among middle age and elderly people: A cross-sectional study in Chongqing, China - Bai, Ruixue; Ying, Xiuquan; Shen, Jieqiang; Wu, Tingting; Lai, Xingyu; Wang, Lingyun; Yu, Meng; Qi, Xiaoya; Mei, Ying (Frontiers in Nutrition, 2022)
Background: The prevalence of hyperuricemia (HUA) has been increasing in recent years. HUA is a crucial risk factor for gout and an independent risk factor for cardiovascular diseases (CVDs). Identifying potentially modifiable factors of HUA is vital for preventing gout and even CVDs. This study aimed to explore the associations of fat distribution with HUA among middle-aged and elderly people in Chongqing, China. Methods: A cross-sectional study was conducted during July 2020 and September 2021. People who underwent quantitative computed tomography (QCT) scans were invited to participate in the study. A total of 3683 individuals whose clinical characteristics and QCT-based fat distribution measurements included visceral fat area (VFA), subcutaneous fat area (SFA), and liver fat content (LFC) were well recorded were included. HUA was defined as having a serum uric acid level greater than 420.0 μmol/L. Multivariate logistic regression models were used to evaluate the association between these adipose variables and HUA prevalence. Results: The HUA prevalence was 25.6% (943/3683), which was 39.6% (817/2063) in men and 7.8% (126/1620) in women. In the fully adjusted model (model 4), the comparison of the highest one with the lowest quartiles of adipose variables showed that the multivariable OR (95% confidence intervals) of HUA were 2.08 (1.36–3.16; P for trend=0.001) for VFA, 0.89 (0.63–1.25; P for trend=0.651) for SFA, and 1.83 (1.42–2.34; P for trend < 0.0001) for LFC. For VFA, the association was more evident in men than in women. Conclusions: Higher VFA and LFC were significantly associated with the increased prevalence of HUA in middle-aged and elderly Chinese individuals. VFA and LFC may have a predictive effect on HUA. Controlling visceral and liver fat accumulation may be beneficial for middle-aged and older people. HUA can be prevented with specific effective healthy physical activity and balanced diet guidelines.